Synthesis and Characterization of Pine-cone Derived Carbon-based Solid Acid: a Green and Recoverable Catalyst for the Synthesis of Pyrano_ pyrazole, Amino-benzochromene, Amidoalkyl Naphthol and Thiazolidinedione Derivatives - Ghorbani, Fatemeh; Pourmousavi, Seied A.; Kiyani, Hamzeh (Letters in Organic Chemistry, 2021)
In this report, SO3H-functionalized Carbon nanoparticles (Pine-SO3H) with high acid density have been synthesized by the thermal treatment of sulfuric acid with Pine-Cone as carbon-based at 180°C in a sealed autoclave in a one-step procedure. The resulted Nanocatalyst was characterized by FT-IR, TGA, XRD, FE-SEM and elemental analysis (EA). The result of characterization was shown that the carbon-based acid is amorphous with polycyclic aromatic carbon sheets attached plentiful -OH, -COOH, and -SO3H groups. The catalytic activities of Pine-SO3H was investigated in the highly efficient synthesis of pyrano[2,3-c] pyrazole, amino-benzochromenes, amidoalkyl naphthol and 5-arylidene-2,4-thiazolidinedione derivatives. The application of Pine-SO3H in the synthesis offers several advantages such as simple procedure with an easy work-up, recoverable catalyst, mild condition, eco-friendliness, excellent yields, short reaction times and use of an inexpensive catalyst.
Keywords: Biomass